2022
DOI: 10.1038/s41594-022-00831-6
|View full text |Cite
|
Sign up to set email alerts
|

The inner nuclear membrane protein Lem2 coordinates RNA degradation at the nuclear periphery

Abstract: Transcriptionally silent chromatin often localizes to the nuclear periphery. However, whether the nuclear envelope (NE) is a site for post-transcriptional gene repression is not well understood. Here we demonstrate that Schizosaccharomycespombe Lem2, an NE protein, regulates nuclear-exosome-mediated RNA degradation. Lem2 deletion causes accumulation of RNA precursors and meiotic transcripts and de-localization of an engineered exosome substrate from the nuclear periphery. Lem2 does not directly bind RNA but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 76 publications
(134 reference statements)
0
16
0
Order By: Relevance
“…The mechanism by which Lem2 promotes heterochromatic silencing remains opaque; although there is evidence that Lem2 influences the balance of recruitment of opposing chromatin factors including the HDAC repressor complex SHREC and anti-silencing Epe1, no physical association of Lem2 with these factors has been detected (Banday et al, 2016; Barrales et al, 2016). Interestingly, very recent evidence indicates that Lem2 can also influence post-transcriptional silencing by interacting with RNA surveillance factor Red1 to regulate RNA degradation by the nuclear exosome (Martin Caballero et al, 2022). An intriguing possibility is that this post-transcriptional mechanism might contribute to Lem2-mediated silencing of the centromeric imr:ura4+ reporter; in future it will be interesting to explore whether Lem2 interaction with Red1 is affected by SUMOylation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanism by which Lem2 promotes heterochromatic silencing remains opaque; although there is evidence that Lem2 influences the balance of recruitment of opposing chromatin factors including the HDAC repressor complex SHREC and anti-silencing Epe1, no physical association of Lem2 with these factors has been detected (Banday et al, 2016; Barrales et al, 2016). Interestingly, very recent evidence indicates that Lem2 can also influence post-transcriptional silencing by interacting with RNA surveillance factor Red1 to regulate RNA degradation by the nuclear exosome (Martin Caballero et al, 2022). An intriguing possibility is that this post-transcriptional mechanism might contribute to Lem2-mediated silencing of the centromeric imr:ura4+ reporter; in future it will be interesting to explore whether Lem2 interaction with Red1 is affected by SUMOylation.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian Lem2 is critical for embryonic development (Tapia et al, 2015), and mutations in LEM2 have been linked to several human diseases including juvenile cataracts, arrhythmic cardiomyopathy, and a novel nuclear envelopathy with progeria-like symptoms (Boone et al, 2016; Abdelfatah et al, 2019; Marbach et al, 2019), highlighting the potential clinical importance of understanding the regulation of Lem2 mediated pathways. In S. pombe , it has previously been suggested that post-translational modification could account for observed differences in Lem2 function in different nutritional conditions (Martin Caballero et al, 2022); it is an intriguing possibility that changes in Lem2 SUMOylation status may mediate the response to environmental cues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations